2023
DOI: 10.1002/mgg3.2251
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a de novo variant in the ASXL2 gene related to Shashi‐Pena syndrome

Abstract: BackgroundASXL2 encodes proteins involved in epigenetic regulation and the assembly of transcription factors at specific genomic loci. Germline de novo truncating variants in ASXL2 have been implicated in Shashi‐Pena syndrome, which results in features of developmental delay (DD), glabellar nevus flammeus, hypotonia, and cardiac disorders. However, the variants are rare, and the clinical spectrum may be incomplete.MethodsThe clinical data such as brain MRI were collect. The whole exome sequencing was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition to their roles in myeloid malignancies, deletion studies in mice have shown that both Asxl1 and Asxl2 regulate hematopoiesis [41][42][43][44]51,52], whereas the role of Asxl3 in hematopoiesis remains unexplored. De novo mutations in ASXL family members are associated with various developmental defects: ASXL1 mutations are linked to BOS, ASXL2 mutations to Shashi-Pena syndrome (SPS), and ASXL3 mutations to BRS [10,[62][63][64][65][66]. ASXL1 mutations leading to BOS are characterized by distinctive facial features, cleft palates, intellectual disability, microcephaly, breathing problems, skeletal abnormalities, and eye defects [10,65,67].…”
Section: Developmental Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their roles in myeloid malignancies, deletion studies in mice have shown that both Asxl1 and Asxl2 regulate hematopoiesis [41][42][43][44]51,52], whereas the role of Asxl3 in hematopoiesis remains unexplored. De novo mutations in ASXL family members are associated with various developmental defects: ASXL1 mutations are linked to BOS, ASXL2 mutations to Shashi-Pena syndrome (SPS), and ASXL3 mutations to BRS [10,[62][63][64][65][66]. ASXL1 mutations leading to BOS are characterized by distinctive facial features, cleft palates, intellectual disability, microcephaly, breathing problems, skeletal abnormalities, and eye defects [10,65,67].…”
Section: Developmental Rolesmentioning
confidence: 99%
“…ASXL1deleted mouse models have defects in kidney podocyte development [69], embryonic fibroblast proliferation [70], and embryonic lung maturation [14]. Germline mutations of ASXL2 cause developmental syndromes, including SPS, characterized by the absence of slowed growth and microcephaly [66,71]. ASXL3 mutations leading to BRS are associated with intellectual disability, developmental delay, and speech and language difficulties.…”
Section: Developmental Rolesmentioning
confidence: 99%